Review of the book CLIL activities: A resource for subject and language teachers, by L. Dale & R. Tanner - Dario Luis Banegas (Universidad de La Sabana, 2013)
Review of the book CLIL activities: A resource for subject and language teachers (with CD-ROM), by Liz Dale and Rosie Tanner. (2012). Cambridge, England: Cambridge University Press.  v + 284, pp. US$ 32.50 (paperback), ISBN 978-0-521-14984-6 (paperback and CD-ROM).